The interaction of La3+ complexes of DOTA/DTPA-glycoconjugates with the RCA120 lectin : a saturation transfer difference (STD) NMR spectroscopic study - Teixeira, João M. C. (2011)
The study of ligand-receptor interactions using high resolution NMR techniques, namely the Saturation Transfer Difference (STD), is presented for the recognition process between La(III) complexes of DOTA mono(amide) and DTPA bis(amide) glycoconjugates and the galactose specific lectin Ricinus Communis agglutinin (RCA120). This new class of Gd(III)-based potential targeted MRI contrast agents (CAs), bearing one or two terminal sugar (galactosyl or lactosyl) moieties, has been designed for in vivo binding to ASGPR (the asialoglycoprotein receptor), which is specifically expressed at the surface of liver hepatocytes, with the aim of leading to a new possible diagnosis of liver pathologies. The in vitro affinity constants of the divalent La(III)- glycoconjugate complexes to RCA120, used as a simple, water soluble receptor model, were higher than those of the monovalent analogues. The combination of the experimental data obtained from the STD NMR experiments with molecular modelling protocols (Autodock 4.1) allowed us to predict the binding mode of mono and divalent forms of these CAs to the galactose 1 binding sites of RCA120. The atomic details of the molecular interactions allowed corroborating and supporting the interaction of both the sugar moieties and the linkers with the surface of the protein and thus, their contribution to the observed interaction stabilities.